Answer:
Hence final answer is [tex]-\frac{1}{216}[/tex].
Step-by-step explanation:
Expression is not typed in proper format but as per given instruction "evaluate the exponent", I think it is:
[tex]\left(-6\right)^{-3}[/tex]
So let's simplify that:
[tex]\left(-6\right)^{-3}[/tex]
Apply formula x^-m=1/x^m
[tex]=\frac{1}{\left(-6\right)^{+3}}[/tex]
[tex]=\frac{1}{\left(-6\right)^3}[/tex]
[tex]=\frac{1}{\left(-6\right)\left(-6\right)\left(-6\right)}[/tex]
[tex]=\frac{1}{-216}[/tex]
[tex]=-\frac{1}{216}[/tex]
Hence final answer is [tex]-\frac{1}{216}[/tex].